The Relationship of Religious Character to Student Learning Outcomes in Elementary School - Arjusi Arjusi; Rizki Alfiana (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This study aimed to describe the value of religious character on student learning outcomes in Islamic religious learning content in elementary schools. Methodology: This type of research is qualitative descriptive research. This research was conducted at Elementary School 76/I Sungai Buluh with 15 students as research subjects obtained from a random sampling technique. The research instrument used in this study used observation and interview techniques with teachers and students. Main Findings: The results of this study indicate that Islamic religious learning in elementary schools has a major influence. One of them is the implementation of religious character values in learning, which can impact student learning outcomes that lead to the affective domain. With Islamic learning, it is hoped that it will equip students with character values that can become a stronghold for themselves in facing the challenges of the times so that they remain faithful and firm in their beliefs. Novelty/Originality of this study: Linking between affective and cognitive aspects is rarely done by other researchers. Therefore, the researcher took this part to complement the previous research.